Folic acid deficiency enhanced microglial immune response via the Notch1/nuclear factor kappa B p65 pathway in hippocampus following rat brain I/R injury and BV2 cells. Issue 7 (13th May 2019) - Cheng, Man; Yang, Liu; Dong, Zhiping; Wang, Mengying; Sun, Yan; Liu, Huan; Wang, Xuan; Sai, Na; Huang, Guowei; Zhang, Xumei
Abstract: Recent studies revealed that folic acid deficiency (FD) increased the likelihood of stroke and aggravated brain injury after focal cerebral ischaemia. The microglia‐mediated inflammatory response plays a crucial role in the complicated pathologies that lead to ischaemic brain injury. However, whether FD is involved in the activation of microglia and the neuroinflammation after experimental stroke and the underlying mechanism is still unclear. The aim of the present study was to assess whether FD modulates the Notch1/nuclear factor kappa B (NF‐κB) pathway and enhances microglial immune response in a rat middle cerebral artery occlusion‐reperfusion (MCAO) model and oxygen‐glucose deprivation (OGD)‐treated BV‐2 cells. Our results exhibited that FD worsened neuronal cell death and exaggerated microglia activation in the hippocampal CA1, CA3 and Dentate gyrus (DG) subregions after cerebral ischaemia/reperfusion. The hippocampal CA1 region was more sensitive to ischaemic injury and FD treatment. The protein expressions of proinflammatory cytokines such as tumour necrosis factor‐α, interleukin‐1β and interleukin‐6 were also augmented by FD treatment in microglial cells of the post‐ischaemic hippocampus and in vitro OGD‐stressed microglia model. Moreover, FD not only dramatically enhanced the protein expression levels of Notch1 and NF‐κB p65 but also promoted the phosphorylation of pIkBα and the nuclear translocation of NF‐κB p65. Blocking of Notch1 with N‐[N‐(3, 5‐difluorophenacetyl)‐l‐alanyl]‐S‐phenylglycine t‐butyl ester partly attenuated the nuclear translocation of NF‐κB p65 and the protein expression of neuroinflammatory cytokines in FD‐treated hypoxic BV‐2 microglia. These results suggested that Notch1/NF‐κB p65 pathway‐mediated microglial immune response may be a molecular mechanism underlying cerebral ischaemia‐reperfusion injury worsened by FD treatment.